Determinants of the Entrepreneurial Influence on Academic Entrepreneurship-Lessons Learned from Higher Education Students in Portugal - João M. Lopes; Márcio Oliveira; José Oliveira; Marlene Sousa; Tânia Santos; Sofia Gomes (MDPI AG, 2021)
Academic entrepreneurship is becoming increasingly important to the field of research as well as to policy makers due to its ability to contribute to the economic, technological, and social development of regions and countries. This research aims to evaluate the determinants that influence the interest of Portuguese higher education students (HEI's) to become entrepreneurs. The methodology used is quantitative and uses structural model equations. The results obtained demonstrate that the student's perception of business skills, business growth skills, strategy, and successful business are key factors that students take into account in their entrepreneurial orientation. The research contributes to this theory by adding new knowledge to the literature on the perception of the HEI's students to become entrepreneurs, specifically the students of Portuguese universities. In practical terms, the contributions offered within this research are based on suggestions for the third mission of universities, explicitly knowledge transfer to the community, business groups, and policy makers, as well as the creation of the essentials within university boundaries to promote entrepreneurship amongst its students. The research is original and innovative, as no research on this field with all the aggregated elements under study has been previously performed in Portugal. Furthermore, the obtained results can translate into ideas that potentially create jobs.